Assessing the Impact of COVID-19 Pandemic on the Domestic Water Usage of Local Communities in Hanoi, Vietnam - Mai, Tran Ngoc; Thi Nuong, Bui; Trang, Vu Quynh (VNU Journal of Science: Earth and Environmental Sciences; Vol 39 No 1DO - 10.25073/2588-1094/vnuees.4900, 2023)
This study aims to better understand the changes in the water usage behaviors of Hanoi communities in the current circumstance of preventing the spread of COVID-19 pandemic and developing the economy. The results of 206 survey responses conducted during April 2022 show that the main changes in the domestic water usage behavior of Hanoi communities come from hand washing, bathing/personal hygiene, house cleaning, and clothes washing. During the pandemic, 77% of the respondents had a habit of washing their hands for 30 seconds as recommended by the Ministry of Health and the frequency of daily hand washing increased 5-7 times compared to before the pandemic. The frequency of housing deep cleaning increased by 33% compared to before the pandemic, besides the frequency of floor mopping also increased about 3.5 times per week. The average frequency of clothes washing also changed from 2.43 times/week to 4.61 times/week. The total estimated moderate water use per person increased by 1.41% compared to its before the pandemic. Therefore, based on the total population of Hanoi city, the amount of domestic water increased by 471.457 m 3 /day. Statistical results show that there are differences in most of the water usage behaviors between the two groups of people living in apartments and houses.